An updated systematic review and meta-analysis on adherence to mediterranean diet and risk of cancer - Morze, Jakub (Eur J Nutr, 2020)
PURPOSE: The aim of current systematic review was to update the body of evidence on associations between adherence to the Mediterranean diet (MedDiet) and risk of cancer mortality, site-specific cancer in the general population; all-cause, and cancer mortality as well as cancer reoccurrence among cancer survivors. METHODS: A literature search for randomized controlled trials (RCTs), case–control and cohort studies published up to April 2020 was performed using PubMed and Scopus. Study-specific risk estimates for the highest versus lowest adherence to the MedDiet category were pooled using random-effects meta-analyses. Certainty of evidence from cohort studies and RCTs was evaluated using the NutriGrade scoring system. RESULTS: The updated search revealed 44 studies not identified in the previous review. Altogether, 117 studies including 3,202,496 participants were enclosed for meta-analysis. The highest adherence to MedDiet was inversely associated with cancer mortality (RR(cohort): 0.87, 95% CI 0.82, 0.92; N = 18 studies), all-cause mortality among cancer survivors (RR(cohort): 0.75, 95% CI 0.66, 0.86; N = 8), breast (RR(observational): 0.94, 95% CI 0.90, 0.97; N = 23), colorectal (RR(observational): 0.83, 95% CI 0.76, 0.90; N = 17), head and neck (RR(observational): 0.56, 95% CI 0.44, 0.72; N = 9), respiratory (RR(cohort): 0.84, 95% CI 0.76, 0.94; N = 5), gastric (RR(observational): 0.70, 95% CI 0.61, 0.80; N = 7), bladder (RR(observational): 0.87, 95% CI 0.76, 0.98; N = 4), and liver cancer (RR(observational): 0.64, 95% CI 0.54, 0.75; N = 4). Adhering to MedDiet did not modify risk of blood, esophageal, pancreatic and prostate cancer risk. CONCLUSION: In conclusion, our results suggest that highest adherence to the MedDiet was related to lower risk of cancer mortality in the general population, and all-cause mortality among cancer survivors as well as colorectal, head and neck, respiratory, gastric, liver and bladder cancer risks. Moderate certainty of evidence from cohort studies suggest an inverse association for cancer mortality and colorectal cancer, but most of the comparisons were rated as low or very low certainty of evidence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00394-020-02346-6) contains supplementary material, which is available to authorized users.